Effects of acid modification of activated charcoal on adsorption of Sevoflurane as an anesthesia gas - Asghar Ghahri; Farideh Golbabaei; Leila Vafajoo; Seyed Mohammad Mireskandari; Mehdi Yaseri; Seyed Jamaleddin Shahtaheri; Faranak Najarian (بهداشت و ایمنی کار, 2018)
Introduction: Anesthetic gases used in hospitals include N2O and halogenated hydrocarbons (such as sevoflurane) which can be released through leakages and uncontrolled exhalation by the patient into the ambient air of clinical staff. These gases have greenhouse effect and damage to the ozone layer and serious risks such as reproductive, preterm delivery and fetal abnormalities and increased spontaneous abortion on the health of operating room personnel. Therefore, removal of these gases from the workplaces is essential especially in the treatment centers. The purpose of the present study was to investigate the adsorption of sevoflurane from air by using activated Charcoal and also the effect of acid modification on its performance.